Bahaya Kumpul Kebo Bagi Para Pemuja Cinta - Angelline Putri Permatasari; Aris Prio Agus Santoso (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The criminalization of cohabitation is a phenomenon that was recently appointed as a criminal offense in the Draft Criminal Code. Cohabitation, also known as "samen leven" or "living in nonmatrimonial union", refers to the act of living together outside of legal marriage. In this analysis, researchers focus on ethical, moral and legal aspects related to the criminalization of cohabitation. This research also examines how the criminalization of cohabitation can be seen as a step in the criminal law reform process which aims to encourage criminal law reform and meet the needs of the times. In this research, researchers also consider how the criminalization of cohabitation can affect the dynamics of Indonesian society and how Indonesian society sets regulations for themselves and for the benefit of the society concerned. This research method uses a normative legal approach and secondary data collection. The results of this research are that the act of cohabitation must be included in a container with clearer regulations, and the act of cohabitation in Indonesia is an act that is prohibited by all religions.